CORROSION RESISTANCE OF PANI/POLYMORPHIC-ZRO2 MODIFIED EPOXY PAINT IN HIGH SALINITY ENVIRONMENT - Munaji, Munaji; Ardika, Rizki Dwi; Ahmad, Nanang Sufiadi; Pratama, Albet Eka; Rifai, Ahmad; Azam, Alfandy Kurnia; Triwikantoro, Triwikantoro (Universitas Mataram, 2025)
Corrosion in high-salinity environments remains a major concern in maintaining the durability and performance of metallic infrastructure. The use of conductive polymers and ceramic nanoparticles, such as polyaniline (PANI) and zirconia (ZrO₂), has emerged as a promising strategy to improve the corrosion resistance of protective coatings. This study aims to evaluate the effect of ZrO₂ polymorphic phases—tetragonal (t-ZrO₂), monoclinic (m-ZrO₂), and a mixture of tetragonal–monoclinic (tm-ZrO₂)—on the corrosion protection performance of PANI/ZrO₂-modified epoxy coatings applied on ST42 steel. The coatings were applied using spray coating. Compositions of ZrO₂ were varied at 2.5%, 5%, 7.5%, and 10% by weight. To simulate a marine environment, corrosion resistance was assessed using Tafel plot measurements in a 3.5% NaCl solution at room temperature. The results revealed that coatings containing t-ZrO₂ and tm-ZrO₂ phases exhibited significantly lower corrosion rates than those with m-ZrO₂. At 7.5% composition, the addition of ZrO₂ reduced the corrosion rate from 0.6710 mpy (without PANI/ZrO2) to 0.3988 mpy (with PANI/m-ZrO2), 0.0364 mpy (with PANI/t-ZrO2) and 0.0212 mpy (with PANI/tm-ZrO2). These findings highlight the critical role of ZrO₂ phase composition in improving coating performance. Incorporating t-ZrO₂ and tm-ZrO₂ into epoxy coatings presents a promising pathway to enhance corrosion resistance, offering valuable potential for applications in aggressive saline environments.